The Alice behind wonderland - Winchester, Simon 1944- (Oxford Univ. Press, 2011)
"In the summer of 1858, in a garden behind Christ Church in Oxford, Charles Dodgson--better known by his pseudonym Lewis Carroll--dressed the six-year-old Alice Liddell in ragamuffin's clothes, and then snapped the camera's shutter. In The Alice Behind Wonderland, Simon Winchester uses the famous photograph of Alice as the launching pad for an appreciative energetic and penetrating look at the inspiration behind, and the making of, one of the greatest classics of children's literature. Indeed, Winchester shows that Dodgson's love of photography deeply influenced his view of the world, helping to transform this shy and half-deaf mathematician into one of the world's best-loved observers of childhood. Much like the fictional Alice's world, as the photograph is subject to closer examination, 'Alice Liddell as The Beggar Maid' becomes curiouser and curiouser, capturing a moment during a golden afternoon that would endure forever. 'Alice Liddell as The Beggar Maid' was, in short, the muse that would inspire the creation of Alice's Adventures in Wonderland. Deftly engaging with Dogson's published writings, private diaries, and photography, Winchester weaves together the poignant, turbulent, and entirely fascinating story behind Lewis Carroll and the making of his Alice. Acclaim for Simon Winchester "An exceptionally engaging guideat home everywhere, ready for anything, full of gusto and seemingly omnivorous curiosity." --Pico Iyer, The New York Times Book Review "A master at telling a complex story compellingly and lucidly." --USA Today "Extraordinarily graceful." --Time "Winchester is an exquisite writer and a deft anecdoteur." --Christopher Buckley "A lyrical writer and an indefatigable researcher." --Newsweek"--
Keywords: Carroll, Lewis / 1832-1898 / Alice's adventures in Wonderland; Carroll, Lewis / 1832-1898 / Photograph collections; Hargreaves, Alice Pleasance Liddell / 1852-1934; Hargreaves, Alice Pleasance Liddell -- 1852-1934; Carroll, Lewis -- 1832-1898; Carroll, Lewis -- 1832-1898 -- Alice's adventures in Wonderland; Geschichte 1800-1900; Fantasy fiction, English / History and criticism; Children's stories, English / History and criticism; Alice (Fictitious character : Carroll); HISTORY / Europe / Great Britain; LITERARY CRITICISM / Children's Literature; LITERARY CRITICISM / General; Alltag, Brauchtum; Vorlage; Great Britain / Social life and customs / 19th century; Europa; Großbritannien